A Facile Synthesis and Antitumor Activity of Novel 2-Aryl-2, 3- dihydro-1H-pyrrolo[3, 4-b]quinoxalin-1-ones. (9th August 2022) - Xi, Qian; Jiang, Wenting; Wang, Hongxue; Liu, Jia; Sun, Fuze; Wen, Baohan; Zhao, Xinyue; Gao, Siyang; Li, Yang
Abstract: In the present investigation, a simple and facile synthesis of a range of structurally novel and intriguing quinoxaline-based isoindolin-1-ones 7a-q has been described through the one-step reaction of ethyl 3-bromomethylquinoxaline-2-carboxylate with arylamines or aliphatic amines in refluxing ethanol medium. A preliminary screening for their in vitro anti-tumor activity against A549 and HT29 using the MTT assay revealed that halo-substituted (F, Cl, Br, I) compounds 7h-k showed promising inhibitory activity, among which fluro-substituted 7h possessed the best activity against the two cell lines with the IC50 values of 1.50 and 3.77 μg/mL, respectively, being much better than the reference Cisplatin. The molecular docking simulation was performed to position compound 7h into the EGFR active site to determine the probable binding model.